PENGARUH SUDUT PEMASANGAN CERUCUK GELAM TERHADAP DAYA DUKUNG PONDASI DANGKAL PADA TANAH GAMBUT - Ghina Amalia; Utari Sriwijaya Minaka; Rani Adinda (TEKNIKA: Jurnal Teknik, 2022)
Peat soil is classified as problem soil with low bearing capacity that must be given a reinforcement before built any construction on it. One of the reinforcementgiven to peat soil is cerucuk gelam. This research conducted a laboratory-scale loading test on a steel plate which was reinforced with the arrangement of the cerucuk gelam with variations in the installation angle of 90o 85o 75o to the shallow foundation plane to see how the influence of the installation angle on the value of the shallow foundations’s bearing capacity on peat soil. This test produced the value of shallow foundations’s bearing capacity, BCR (Bearing Capacit Ratio) and the increasment persentage of BCR. The results of this research indicate tha the highest bearing capacity was 40,22 kPa achieved in the variation of reinforcment that the installation angle of 75o to the shallow foundation plane, the BCR value was 7,55 and the increasment persantage of BCR was 654,6 %.Based on all the tests carried out, it was known that bearing capacity was increase inversely proportional to the installation angle of cerucuk gelam. Key word: Bearing capacity, peat soil, soil reinforcement, cerucuk